Susceptibility of South African dry bean cultivars to bacterial diseases - Fourie, D. (African Crop Science Society, 2011)
Dry beans are an important crop in South Africa with the annual bean consumption being approximately 120 000 t. The crop is annually subjected to a number of biotic constraints such as bacterial diseases that can cause serious yield losses especially when the climate is conducive to diseases. The use of resistant varieties is an effective way of reducing the risk of crop failure and deployment of resistance requires knowledge on the susceptibility of cultivars. Twenty-one locally grown commercial dry bean cultivars were evaluated at Potchefstroom in South Africa to evaluate the resistance to common bacterial blight, halo blight and bacterial brown spot. Results indicated that South African cultivars differed in susceptibility to bacterial diseases. Cultivars Teebus, Cerillos, PAN 146 and PAN 159 were most susceptible to common bacterial blight with Monati and OPS-RS2 having low levels of resistance. Negative correlations (r=-0.44) (P<0.001) between disease ratings and yields were obtained in the common bacterial blight trial. Levels of resistance to halo blight were observed with small seeded cultivars generally being more resistant than large seeded types. A negative correlation (r=-0.35)(P=0.001) was obtained between halo blight rating and yield. Cultivars differed regarding susceptibility to bacterial brown spot with the majority having adequate resistance. Teebus, Cerillos, Bonus and PAN 159 were most susceptible, with Mkuzi exhibiting highest levels of resistance. No correlation was obtained between disease rating and yield. Although a number of cultivars exhibited field resistance to halo blight and bacterial brown spot, all cultivars were more or less susceptible to common bacterial blight. Common bacterial blight can be considered the most important bean bacterial disease in South Africa. Improvement of common bacterial blight resistance in South African cultivars is necessary for yield stability.